The relationship of quantitative epidermal growth factor receptor expression in non-small cell lung cancer to long term survival. - Veale, D. (Nature Publishing Group, 1993)
Increased expression of epidermal growth factor receptor (EGFr) has been reported in non small cell lung cancers (NSCLC) when compared to normal lung. We have examined post-operative survival in 19 surgically treated patients with NSCLC who had full characterisation of EGFr on primary tumour membrane preparations from resection specimens. There were ten squamous, seven adeno and two large cell carcinomas. The median concentration of high affinity sites was 31 fmol per mg of protein (4-1532) and the median dissociation constant (Kd) of these high affinity sites was 2.3 x 10(-10) per mol (1.2-30 x 10(-10)). Seven patients survived over 5 years. Twelve patients died between 8.5 and 55 months from the time of surgery. When > 5 year survivors were compared to non-survivors there was no difference as regards tumour size or stage, or as regards age or sex. The survivors had a median concentration of high affinity EGFr sites of 16.1 fmol mg-1 protein compared to a median concentration of 68.6 fmol mg-1 protein in the non-survivors (P = 0.01 Wilcoxon test). No long term survivor had > 35 fmol mg-1 protein of receptor. Thus EGFr quantitation may give independent prognostic information in NSCLC and help to select patients for adjuvant therapy after surgery. These results need confirmation in a larger prospective study.